Evaluation of oxidant, antioxidant, and S100B levels in patients with conversion disorder - Buyukaslan H; Basmacı Kandemir S; Asoğlu M; Kaya H; Mehmet Tahir Gokdemir MT; Karababa I; Güngörmez F; Kılıçaslan F; Şavik E (Neuropsychiatric Disease and Treatment, 2016)
Hasan Büyükaslan,1 Sultan Basmacı Kandemir,2 Mehmet Asoğlu,3 Halil Kaya,4 Mehmet Tahir Gökdemir,1 İbrahim Fatih Karababa,3 Fatih Güngörmez,5 Fethiye Kılıçaslan,6 Emin Şavik7 1Department of Emergency Medicine, Faculty of Medicine, Harran University, 2Department of Psychiatry, Balıklıgöl State Hospital, 3Department of Psychiatry, Faculty of Medicine, Harran University, Sanliurfa, 4Bursa Yüksek Ihtisas Training and Research Hospital, Bursa, 5Department of Emergency Medicine, Mehmet Akif İnan Research Hospital, 6Department of Child and Adolescent Psychiatry, 7Department of Biochemistry, Faculty of Medicine, Harran University, Sanliurfa, Turkey Introduction: Various psychodynamic, neurobiological, genetic, and sociocultural factors are believed to be involved in the etiology of conversion disorder (CD). Oxidative metabolism has been shown to deteriorate in association with many health problems and psychiatric disorders. We evaluated oxidative metabolism and S100B levels in the context of this multifactorial disease.Methods: Thirty-seven patients with CD (25 females and 12 males) and 42 healthy volunteers (21 females and 21 males), all matched for age and sex, were included in this study. The total oxidant status, total antioxidant status, oxidative stress index, and S100B levels were compared between the two groups.Results: The total oxidant status, oxidative stress index, and S100B levels were significantly higher in patients with CD than in the control group, whereas the total antioxidant status was significantly lower.Conclusion: CD is associated with deterioration of oxidative metabolism and increased neuronal damage. Keywords: conversion disorder, oxidative stress, S100B